The use of information and technology to trace the epidemiological profile of children with leprosy in the state of Paraíba by using the DATASUS repository - Meneses, Nathalia Barros; Marys de Souza e Silva, Pollianna (Informação em Pauta, 2020)
In this century the information is considered of great relevance. Managers and technicians using information, and eventually making use of processing technologies, can create epidemiological profiles and subsidize the construction of relevant public policies for each region. The research aims to determine the epidemiological situation of leprosy in Paraíba in children less than 15 years of age, through the data available in the DataSUS repository. This is a descriptive and retrospective epidemiological study of quantitative nature, having as population of the study all cases of leprosy in children aged 15 years or less in the state of Paraíba, diagnosed and notified in SINAN, during the period 2010-2015. We found 207 new cases (CN) of leprosy in children, with 6% (13) children´s between the ages of 10 and 14. These data prove the endemic level of Paraíba in the period evaluated making clear the need to actively seek suspected cases in children under 15 years and that health professional turn their attention to these age groups, for the early and timely detection of cases.